Where are the opportunities for accelerating food systems innovations for healthier diets? Findings and lessons from Viet Nam - Johnson, Nancy L.; Wyatt, Amanda; Nguyen, Trang (International Food Policy Research Institute, 2021)
This paper examines how research on the impacts of food systems innovations can accelerate their contributions to healthier diets and to equitable and sustainable food systems more generally. Building on research from the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) flagship on Food Systems for Healthier Diets, the paper looks at how evidence from past studies of the impacts of food systems innovations on diet-related outcomes maps to current food system priorities in Viet Nam, one of the program’s focus countries. It then explores what the studies can tell us about the impact pathways from innovations to healthier diets and other outcomes. The findings highlight some promising innovations that have potential for further research and scaling. A revised impact pathway is also proposed based on a new understanding of how the concept of the food environment can be integrated into an impact pathway framework. The new impact pathway and associated assumptions—taken together, the theory of change—can support better understanding and analysis of the impacts of food system innovations on diets.